THE DUAL ROLE OF SINGLE PARENT: A SOCIOLOGICAL STUDY - Pangaribuan, Rina Marta Uly; Resdati, Resdati; Marnelly, T Romi (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This study aims to determine the multiple roles and constraints faced by single parents of women in the midst of their families. This study used qualitative research methods. Research subjects were taken using a purposive sampling technique. Data was collected through observation techniques, interviews and documentation. The theory used is role theory with the supporting theory of AGIL (Adaptation, Goal, Integration, Latency). It was concluded that the role attached to a mother, namely the domestic role and the role attached to a father, namely the public role, has different challenges and implementation. A single-parent woman carries out both roles simultaneously, there is a division of labor among other family members and some are not. There are several forms of maintenance carried out by a single-parent woman in the midst of her family, which will require a time-consuming process. This is done in order to support the current situation and minimize constraints and conflicts in the family. There are several obstacles faced, most of the obstacles are related to meeting family needs, and giving affection and attention. The concept of AGIL in research is associated with the concept of roles and constraints in carrying out these dual roles.